SAFARI - RANDOMISED TRIAL ON COMPLEX THERAPY OF ARTERIAL HYPERTENSION AND DISLIPIDEMY. THE MAIN RESULTS - S. Y. Martsevich; N. P. Kutishenko; V. V. Yakusevich; A. D. Deev; A. A. Serazhim; T. V. Bobkova; L. P. Volkonskaya; V. P. Voronina; N. A. Dmitrieva; O. V. Lerman; J. V. Lukina; M. A. Maksimova; et al. (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate possibility of complex pharmaceutical effect simultaneously on 2 risk factors – arterial hypertension (HT) and hypercholesterolemia (HH) in patients with high risk of cardiovascular complications (CVC).Material and methods. 101 patients with HT of 1-2 stage, HH and high risk of CVC (SCORE>5) were included in the study. Patients were randomized in 2 groups: active therapy group (ATG) and control group (CG). ATG patients were actively treated for HT and HH control. The long-acting nifedipine (Nifecard XL, LEK) 30 mg once daily (OD) was prescribed as start antihypertensive drug. Hydrochlorothiazide 12,5 mg/day OD and bisiprolol 5 mg OD was added if antihypertensive effect was insufficient. Atorvastatin (Tulip, LEK) 20-40 mg OD was prescribed for HH control. Management of CG patients was performed by doctors of out-patient clinics. The study duration was 12 weeks.Results. Systolic and diastolic blood pressure (BP) levels in ATG patients were lower than these in CG patients. Target BP level was reached in 88,4% of ATG patients and only in 48,9% of CG patients. Cholesterol of low density lipoprotein (CH LPLD) level was also lower in ATG patients than this in CG patients. Target CH LPLD level was reached in 37,2 % of ATG patients and in 8,3 % of CG patients. Relative risk of CVC was significantly lower in ATG patients than this in CG patients.Conclusion. SAFARI trial shows that effective pharmaceutical simultaneous control of 2 key risk factors, HT and HH, results in risk reduction of CVC.